(untitled) (Journal of Contemporary Philology, 2024)
The Western European civilizational and colonial paradigm has recognized and inscribed otherness in the wild, impulsive, sexually potent and aggressive barbarian, described in John Maxwell Coetzee’s novel Waiting for the Barbarians. But Fortress Europe – on whose borders millions of Middle East refugees and migrants survive today – is not only the destination that the Other desperately desires, but also the place where his death takes place. The first perception of Europe represents the "zone of existence", the second "the zone of non-existence". One belongs to the citizens (the humans), the other to the "non-citizens" (the subhumans) - refugees, migrants, asylum seekers, the displaced, the discriminated - whose "bare existence" invalidates the contemporary understanding of subjectivity. Excluded from the system, the subhumans represent the constitutive non-part of Europe today. They are the differАnce of the "European apartheid", an external dialectic of its symbolic order, whose false humanitarianism reveals its dark colonial and racist face. This text attempts to show how, eventually, European politics is self-destructive, and its biopolitical system – thanatopolitical, because (being the essence of neoliberalism) the "death of the political" implies death itself.